Murder at the Kennedy Center - Truman, Margaret, 1924-2008. (New York : Random House, 1989)
It is presidential election time and a gala is being prepared for a leading candidate with entertainment and a surprise murder.
Booklist.
Wilson's Fiction.
Adult.
Adult
Keywords: Mystery fiction; Detective and mystery stories